(untitled) (Journal of actual problems of jurisprudence, 2018)
In the work presented, a comprehensive analysis of crimes against information security is conducted. The task is to clarify their concept and system, to consider the optimization of criminal law regulation. The author singles out information security as an independent object of criminal-legal protection. The author substantiates the provision that information security can act as the main and additional object of encroachment. The relevance of the chosen topic is evidenced by the fact that the fight against crimes in the information sphere is one of the main tasks of the law enforcement bodies of not only Kazakhstan but other countries. The author analyzes the positive foreign experience of developing national strategies for ensuring cybersecurity. In this aspect of scientific interest is the analysis of legislative initiatives and mechanisms that ensure cybersecurity in the United States. In the framework of the work, the current trends in information security strategies in such advanced European countries as the United Kingdom, Germany, France, Sweden, Switzerland and others are described in detail.The possibilities of using the accumulated foreign experience in the domestic criminal legislation are analyzed. The article formulates proposals for further improvement of the criminal legislation of the Republic of Kazakhstan in this direction. Key words: information security, cybersecurity, a national strategy for combating crime, criminal offenses against information security, criminal liability.